"Argentina's National Style: Maradona, Peronism, and Metaphysical Football.". (April 2023) - Novoa, Adriana; Koch, Robert
This essay analyzes how Peronist politics explain the emergence of Diego Maradona as a player that represented authentic Argentine football. We explain how the political radicalism popular during his formative years impacted his role in affirming Argentina's national style of play. In doing so, this article also engages scholarship that historicizes the myths of his nation's football. We analyze Maradona's development as a historically situated phenomenon, and argue that, through Peronism, he understood this sport as a metaphysical game that expressed class struggle and the emancipatory aspirations of the poor boys who were seen as creators of the national style. By this, we mean that he focused on the ball and the relationship he was able to establish with it to question reality, possibilities, and even its existence, creating an experience for spectators that was different and sublime, that made football more than a sport.